Analisis Penjualan Produk Aspal Kilang Minyak Pertamina RU IV Cilacap Dengan Metode Statistik - Aly Rasyid; Abdullah Rizky Agusman; Angellita Meisya Dellila (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2023)
The development of road infrastructure such as highways, toll roads, airports, ports, bridges and other infrastructure requires an average of 1.2 million tons of asphalt per year. Under these conditions, the need for domestic asphalt is very large. Asphalt products are one of the petroleum derivative products that have high economic value and are the main raw material in infrastructure development. This research focuses on Pertamina RU IV Cilacap Oil Refinery Asphalt products with 60/70 penetration specifications that have been adapted to the needs and conditions of Indonesia with a tropical climate and are one of the superior products at PT Patra Trading. The purpose of this study is to analyze the simultaneous and partial significant effects using quantitative methods, namely statistical models on SPSS software version 25.0. The parameters used as research variables in the questionnaire to support this research are product excellence, product application, and product quality. Product excellence is a factor that makes a product have value and advantages in the eyes of customers, product application is the process of using products to meet customer needs, and product quality is the ability of a product to meet specifications to increase customer satisfaction. The results showed that the variables of product excellence X1 and product application X2 had a simultaneous effect on the product quality parameter Y based on the F (Simultaneous) test which serves to measure the goodness of fit of the regression equation or determine whether all the independent variables contained in the equation jointly affect the dependent variable by producing a significance value of 0.00 <0.05. Based on the T test (Partial) which serves to test how far the influence of one independent variable individually in explaining the variation in the dependent variable by producing a T-count value of 8.157> T-table 2.02 with a significant level of 0.000 < 0.05 or a significant value smaller than 0, 05 which indicates that there is a significant and partial influence on the Product Excellence variable X1 on Product Quality Y and T-count 6,528> T-table 2.02 with a significant level of 0.000 <0.05 or a significant value smaller than 0.05 there is a significant and partial influence on the Product Application variable X2 on Product Quality Y. Based on the coefficient of determination test which serves to measure how much variation in the independent variable can explain the dependent variable which shows the independent variable Product Excellence X1 and Product Application X2 affect the dependent variable Product Quality by 91.9%.